Aerial photoluminescence imaging of PV modules - Doll, Bernd; Wittmann, Ernst; Lüer, Larry; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2023)
On-site imaging of photovoltaic systems requires methods that are high-throughput, low-cost and contact free for commercial relevance. Photoluminescence imaging satisfies these requirements, but it has so far not been used for aerial imaging due to a lack of a drone-mounted system. In this study, we present first results captured by our in-house developed PLAI (photoluminescence aerial imaging) setup. The setup consists of a hexacopter aerial drone equipped with an illumination unit and a near infrared camera. The unit is capable of partially illuminating full size modules at night and capturing the photoluminescence response. We show that the setup can be used to detect and identify defects such as cracks and potential-induced degradation with high levels of confidence.
CRIS-Team Scopus Importer:2024-12-16